Quaternionic Version of Rotation Groups - Rahmawati, Latief; Ardhi Khalif, Muhammad; Farchani Rosyid, Muhammad (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2015)
Quaternionic version of rotation group SO(3) has been constructed. We constructa quatenionic version of rotation operation that act to a quaternionic version of aspace coordinate vector. The computation are done for every rotation about eachcoordinate axes (x,y, and z). The rotated quaternionic space coordinate vector con-tain some unknown constants which determine the quaternionic rotation operator.By solving for that constants, we get the expression of the quaternionics versionof the rotation operator. Finally the generators of th